KONSEP MOTIVASI BELAJAR MENURUT IMAM AS-SYARKAWI DAN RELEVANSINYA DENGAN PEMBELAJARAN PAI - Munaweroh, Lailatul; Muhlis, Achmad (Bayani, 2025)
Learning motivation is one of the key factors determining the success of the educational process. It serves as a driving force, a guide, and a reinforcement for learning behavior, making its presence essential in every educational activity. This article aims to examine the concept of learning motivation according to Imam As-Syarkawi and its relevance to Islamic Religious Education (PAI). The method employed is a library study by reviewing Imam As-Syarkawi’s works and related literature on both classical and modern perspectives of learning motivation. The study reveals that Imam As-Syarkawi defines motivation as an impulse arising from both physical and spiritual needs that drives individuals toward specific goals. Motivation, in his view, originates from internal factors such as human nature (fitrah), faith, and intention, as well as external factors such as teachers, the learning environment, rewards, and punishments. The ultimate purpose of learning motivation, according to him, is not merely academic achievement but also self-perfection and closeness to Allah SWT. The relevance of this concept to Islamic Religious Education can be seen in four aspects: fulfilling students’ spiritual needs, integrating internal and external factors through the teacher’s role, applying targhib (encouragement through promised rewards) and tarhib (warning through threats of sin) as incentives, and orienting learning motivation toward shaping faithful and virtuous Muslim personalities. Thus, Imam As-Syarkawi’s thought provides both theoretical and practical foundations for fostering holistic learning motivation in Islamic education